A Multivariate Analysis of Diachronic Variation in A Bunch of noun: A Construction Grammar Account. (June 2019) - Shao, Bin; Cai, Yingying; Trousdale, Graeme
On the basis of data retrieved from the Corpus of Historical American English, this paper provides a multivariate analysis of diachronic change in collocations of the sequence a bunch of followed by a noun in the Late Modern and contemporary English periods. Our results show that (1) the partitive semantics shifts in the period from the 1910s to the 1960s from the original dominant meaning 'bundle' to 'group, ' while the quantifier function/'large quantity' meaning of bunch becomes more entrenched from the 1970s onwards, though the three meanings continue to co-exist in the contemporary language; and (2) there exist statistically significant correlations between semantic, pragmatic, and discourse properties of the noun collocates in the partitive and quantifier constructions. While much work on diachronic construction grammar is concerned with the question of how new constructions come into being, the present article complements such research by providing a detailed account of the nature of persistence of the earlier partitive construction and the embedding and gradual entrenchment of the newer quantifier construction. It therefore addresses the consequences of "constructionalization" on a source construction, and the nature of frequency effects in "post-constructionalization" changes.